1973
DOI: 10.1093/brain/96.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Axoplasmic Flow in Axonal Neuropathies I. Axoplasmic Flow in Cats With Toxic Neuropathies

Abstract: INTRODUCTION THE passage of large amounts of protein and other compounds from the nerve cell body down the axon is a widely accepted phenomenon to which the term axoplasmic flow has been applied (see Barondes, 1967). Substances may also travel in a retrograde fashion from the periphery of the axon to the neuron (Lubinska,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The present study of slow and fast anterograde axonal transport of labelled proteins in acrylamide intoxicated rats has shown that the slow transport velocity is normal in animals with severe motor incoordination, as well as in those with only mild signs of neuropathy. In accordance with this finding, a normal transport velocity was reported by Bradley and Williams (1973) and by Sumner et al (1976) from studies on sciatic sensory nerves of cats with acrylamide neuropathy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study of slow and fast anterograde axonal transport of labelled proteins in acrylamide intoxicated rats has shown that the slow transport velocity is normal in animals with severe motor incoordination, as well as in those with only mild signs of neuropathy. In accordance with this finding, a normal transport velocity was reported by Bradley and Williams (1973) and by Sumner et al (1976) from studies on sciatic sensory nerves of cats with acrylamide neuropathy.…”
Section: Discussionsupporting
confidence: 81%
“…It is a new observation of the present study that a decreased fractional amount of protein label is carried in SCa of severely disabled animals. This finding possibly explains the almost historic controversy between the study of Pleasure et al (1969) and that by Bradley and Williams (1973). In the former study a decreased amount of activity was found by autoradiography of cat sensory and motor roots a few days after labelling, whereas the latter study showed SC profiles moving at a normal velocity in sensory fibres of the same model.…”
Section: Discussionmentioning
confidence: 83%
“…However, Bradley and Williams [34] found no diminution in slow axonal transport in acrylamidetreated animals. They did find a decrease in the velocity of the crest of fast axoplasmic transport but did not believe that this reduction was responsible for distal degeneration.…”
Section: Discussionmentioning
confidence: 91%
“…This leads to a depletion in the amount of material reaching the distal regions of axons where degeneration begins (36,38). Another hypothesis suggests that acrylamide inactivates the axonal transport system by which substances, assembled in the neuron cell body, are transported along the axon (39,40). Finally, it has been suggested that if acrylamide inactivated a substance in the axon, which is dependent for its supply on the nerve cell body, this alone could account for the dying-back process (7,27,28).…”
Section: Site Of Neurotoxic Actionmentioning
confidence: 99%